Risk analysis on bond mutual funds in Malaysian market / Suhaily Maizan Abdul Manaf - Abdul Manaf, Suhaily Maizan (2007)
Unit trusts or also known as mutual funds have been considered as good instruments for medium to long-term financial plans. The unit trust industry in Malaysia was first established by British investors in 1959 with the introduction of the Malayan Unit Trust Ltd. The first two decades in the history of the unit trust industry were characterized by slow growth in the sales of units and a lack of public interest in the new investment product. Only five (5) unit trust management companies were established, with a total of 18 funds introduced over that period. The industry was regulated by several parties including the Registrar of Companies, The Public Trustee of Malaysia, Bank Negara Malaysia and the Ministry of Domestic Trade and Consumer Affairs. The 1970s also witnessed the emergence of state government sponsored unit trusts, in response to the Federal Government's call to mobilize domestic household savings. (Fauziah and Mansor, 2007).